2022
DOI: 10.3390/jrfm15010021
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Digital Transformation on Performance: Evidence from Vietnamese Commercial Banks

Abstract: The role of digital transformation in creating value for commercial banks has been interesting to researchers for a long time. While many commercial banks have significantly investigated digital transformation, researchers and managers have still met many difficulties examining the distribution of digital transformation to business performance. This paper aims to evaluate the impact of digital transformation on Vietnamese commercial banks’ performance by different sizes, from there proposing policy implication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 27 publications
6
24
0
1
Order By: Relevance
“…The market share of the individual banks were effected due to the adoption of neobanking. This is consistent with past studies where digital transformation was significant in explaining bank performance (Do et al, 2022;Wadesango and Magaya, 2020;Gupta et al, 2020). Significance of the interest rate also corroborates that monetary policy had an impact of on market share of the banks.…”
Section: Emirates Nbd (Enbd)supporting
confidence: 91%
See 2 more Smart Citations
“…The market share of the individual banks were effected due to the adoption of neobanking. This is consistent with past studies where digital transformation was significant in explaining bank performance (Do et al, 2022;Wadesango and Magaya, 2020;Gupta et al, 2020). Significance of the interest rate also corroborates that monetary policy had an impact of on market share of the banks.…”
Section: Emirates Nbd (Enbd)supporting
confidence: 91%
“…Digital transformation, in terms of capital and development level of science and technology, has been shown to have a positive effect on performance of Vietnamese commercial banks and the impact was greater for larger commercial banks (Do et al, 2022). This was confirmed by Gupta et al, (2020) who showed that digitalization leads to better performance as it can increase productivity and decrease costs.…”
Section: Literature Reviewmentioning
confidence: 85%
See 1 more Smart Citation
“…In another study by Stefanovic et al (2021), the relationship between digitalization and sustainable development in the Serbian banking sector showed that digitalization positively affects banks' return on equity and helps banks remain profitable even under the conditions of the global COVID-19 pandemic. Finally, Do et al (2022) found that digital transformation has a positive effect on the work of Vietnamese commercial banks, and the strength of the positive influence is directly proportional to the scale of the bank. Based on these arguments, there is mixed evidence of the relationship between economic growth, Banks Credit to the Private Sector and digitalization; hence this study examines the moderating role of digitalization in the relationship between economic growth and bank credit to the private sector.…”
Section: Economic Growth Banks' Credit To Private Sector and Digitali...mentioning
confidence: 98%
“…For a long time, experts have been curious about how digital transformation affects commercial banks' ability to create value. The distribution of digital transformation to company performance has proven to be a challenge for researchers and managers even though many commercial banks have invested significant time and resources into the topic (Do et al, 2022).…”
Section: Introductionmentioning
confidence: 99%